Analisa Balancing Rotor Terhadap Resiko Kerusakan Turbocharger Lokomotif Diesel - damayanti, ajeng tyas (Politeknik Perkeretaapian Indonesia Madiun, 2021)
This research was conducted with the aim of looking at the level of effectiveness of the balancing rotor on the turbocharger component and knowing the effect of the balancing rotor on the risk of damage to the turbocharger. The data used is primary data in the form of the results of the initial and final balancing of the turbocharger rotor. The data is used to determine the level of effectiveness of the balancing that has been done. Data from interviews with Yogyakarta Balaiyasa technicians will show how much influence the balancing has had on the balance of the rotor. From the results of data processing and analysis that has been carried out, it is known that the average percentage of balancing effectiveness on the blower is 91.5%, while the average percentage of balancing effectiveness on the turbine is 94.5%. So the average effectiveness of balancing on both the blower and turbine is 93%. The unbalance tolerance allowed in the balancing process is 0.56 grams. From the results of interviews with Yogyakarta Balaiyasa technicians, it is known that if the unbalance exceeds 0.56 grams it will result in several things including damage to the bearing in the long term because it holds the rotor rotation is not balanced and there is an unstable rotation so that the turbine and casing rub against each other and result in risk. cracked or broken.